Serangga Fitofag dan Entomofag Pada Tanaman Pare (Momordica charantia L) di Kecamatan Indralaya Utara, Kabupaten Ogan Ilir - Hefi Sugiarto, Muhammad; Irsan, Chandra; Warman, Aditya; Laila, Mey Rahma; Nuraini, Feni; Apriliani Putri, Ochi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Sugiarto, M.H., Irsan, C., Warman, A., Laila, M.R., Nuraini, F., Putri, O.A. (2024).Phytophagous and Entomophagous insects on bitter gourd (Momordica charantia L) plants in North Indralaya District, Ogan Ilir Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 843–853). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Phytophagous insects are plant-eating insects or what are usually called herbivores. These phytophagous insects are referred to as pests if their eating behavior on plants causes economic losses. Meanwhile, predatory insects or entomophages are a group of natural enemies that are very important in helping reduce pest populations. This research aims to identify and determine insect species that live on plants or around plants and their role on plants and other insect species. Research was conducted on 2 vegetative and generative bitter melon fields among farmers in North Indralaya District, Ogan Ilir Regency, South Sumatra Province in September 2021. The observation method was carried out using 2 traps, namely the pan trap and the pitfall trap. This observation was carried out every morning at a distance of 12 hours for pan traps and 24 hours for pitfall traps within 1 week. Observations on bitter melon plants show that arthropod species use pan traps. The results obtained were 7 orders, 16 families and 17 species of arthropods on bitter melon plants which were successfully identified using pan traps and 6 orders and 9 families and 8 species of arthropods which were successfully identified using pitfall traps.